A bi-layer electrospun nanofiltration membrane for plasmid DNA recovery from fermentation broths - Correia, Tiago R. (2013)
The demanding ever-increasing quantities of highly purified biomolecules by bio-industries, has triggered the development of new, more efficient, purification techniques. The application of membrane-based technologies has become very attractive in this field, for their high throughput capability, simplicity of operation and scale-up. Herein we report the production of a bi-layer membrane by electrospinning (ES), in which a support of poly ε-caprolactone nanofibers was coated with a polyethylene oxide/sodium alginate layer, and subsequently cross-linked with calcium chloride. The membranes were characterized by SEM, ATR-FTIR, contact angle measurements, and were applied in the recovery process of a plasmid. The results show that membranes retained the suspended solids while allowing the permeation of plasmid DNA, with high recovery yields and improved RNA retention. Moreover, they also showed a very low fouling tendency. To the best of our knowledge it is the first time that ES membranes are applied in this type of bioprocess.